PENGARUH KREATIVITAS MENGAJAR GURU DAN MOTIVASI BELAJAR SISWA TERHADAP KEMAMPUAN MENGHAFAL SISWA DI SD IT AN-NIDA KOTA LUBUKLINGGAU - Niah Elfita Sari (IAIN Bengkulu, 2018)
This study aims to determine the influence of teacher teaching creativity on the students ‘ability to memorize Al- Qur’an, to determine the effect of students’ learning motivation on the students ‘ability to memorize Al-Qur’an to know the influence of teacher’s teaching creativity and student’s learning motivation to students’ ability to memorize Al- Qur’an. The population of this research is the students of class VI A and VI B which amounted to 240 people, while the samples in this study is 25% of the population of 60 people. Based on the discussion of research results that the influence of teacher teaching creativity and students’ learning motivation to the ability to memorize grade 6 students of SD IT AN-NIDA of Lubuklinggau City in 2017, can be summarized as follows: First, there is a significant influence between teachers’ teaching creativity on students’ memorization ability. This is based on the calculation of the correlation between X1 to Y of 0.581 and regression equation Y= 26.619 +0.581. Second, there is a significant influence between students’ learning motivation on the ability to memorize students. This is based on the calculation of the correlation between X2 to Y of 0.033 and regression equation Y = 8.258 +0.033. Third, there is a very significant influence between teacher teaching creativity and student learning motivation jointly or individually to the ability to memorize students. From result of correlation calculation by using multiple regression analysis obtained correlation price of R between X1 and X2 together to Y equal to 0,583 and regression equation Y = 14,684 + 0,587= 0,045.